IDENTIFIKASI LALAT BUAH (Bactrocera spp.) PADA TANAMAN BUAH DI BEBERAPA KABUPATEN PROVINSI RIAU - M. Fahmi A Siregar; Agus Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research objective is to identify the type of fruit flies that attack fruit plan in some regencies in Riau. Fruits used in this research are: mango, orange, chili, guava, brown, leatherback and jackfruit. The research was conducted in laboratory of Agricultural Quarantine Class I Pekanbaru. This type of research is an exploratory description that describes data was collected in the field by using the method of trap. Once the fruit fly was trapping in trap, then it is collected and finally identified for further identification. The results showed that from the identification, there are six types of fruit flies that attack fruits are Bactrocera carambolae, Bactrocera papayae, Bactrocera umbrosa, Bactrocera cucurbitae, Bactrocera albistrigata dan Bactrocera tau. Keywords: Fruit flies, regency, fruit.